Synthesis and Antimicrobial Evaluation of Some New Fluoro Formazans - Avinash Taterao Shinde; N. J. Deshmukh; G. D. Kottapalle; S. B. Zangade (The Journal of Pure and Applied Chemistry Research, 2016)
A series of fluoro substituted formazan derivatives has been synthesized from the salt of diazonium chloride & fluoro schiff base in pyridine. The structure of newly synthesized formazans were established based on IR, 1H NMR and mass spectral data. All the synthesized compounds were screened for their antimicrobial activity. Some of the compounds showed very good activity compared to standard drugs against all pathogenic bacteria and fungi.